Two-sided matching via balanced exchange: Tuition and worker exchanges - Umut Mert Dur; M. Utku Ünver (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
We introduce a new matching model to mimic two-sided exchange programs such as tuition and worker exchange, in which each firm has to avoid being a net-exporter of workers. These exchanges use decentralized markets, making it difficult to achieve a balance between exports and imports. We show that stable equilibria discourage net-exporting firms from exchange. We introduce the two-sided top-trading-cycles mechanism that is balanced-efficient, worker-strategy-proof, acceptable, and individually rational, and respects priority bylaws regarding worker eligibility. We prove that it is the unique mechanism fulfilling these objectives. Moreover, it encourages exchange, since full participation is the dominant strategy for firms.
Keywords: C71; C78; D71; D78; 330; Market Design; Matching Theory; Tuition Exchange; Worker Exchange; Balanced Exchange; Two-sided Matching; Two-sided Top Trading Cycles